1972
DOI: 10.1139/y72-150
|View full text |Cite
|
Sign up to set email alerts
|

Human Skeletal Muscle Phosphorylase Activities with Exercise and Training

Abstract: Fifteen healthy male subjects classified as sedentary (7) or active (8), exercised to exhaustion on a bicycle ergometer at a work load requiring 70% of their maximal aerobic capacity. Biopsy samples of the vastus lateral is muscle were taken at rest, at the time of fatigue, and after a 10 min recovery. Training increased [Formula: see text], [Formula: see text], work time to fatigue, skeletal muscle glycogen levels, and phosphorylase a activity (P < 0.01). An exhaustive submaximal exercise reduced the glyco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1974
1974
1990
1990

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…All these adaptations contribute to the increased lipid metabolism and 'glycogen sparing' reported for a given submaximal workload following training. In apparent contradiction to these adaptations, Taylor et al (1972b) reported that phosphorylase activity was significantly increased by endurance training. Taylor et al (1971) also re->,orted that glycogen utilisation was greater following training for a work regimen in which the subjects worked at between 60 and 80% V02max.…”
Section: Glycogen Response To Endurance Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…All these adaptations contribute to the increased lipid metabolism and 'glycogen sparing' reported for a given submaximal workload following training. In apparent contradiction to these adaptations, Taylor et al (1972b) reported that phosphorylase activity was significantly increased by endurance training. Taylor et al (1971) also re->,orted that glycogen utilisation was greater following training for a work regimen in which the subjects worked at between 60 and 80% V02max.…”
Section: Glycogen Response To Endurance Trainingmentioning
confidence: 99%
“…Finally, phosphorylase a activity is significantly reduced by fatiguing endurance activity in trained and untrained individuals (Taylor et al 1972b). …”
Section: Acute Glycogen Response To Endurance Exercisementioning
confidence: 99%
“…There have been few quantitative studies of phosphorylase activity in human skeletal muscle (2, 5, 18,21) and in only one of these (2) was the enzyme assayed in the direction of glycogen breakdown. This latter study was made using samples of m. erector trunci.…”
mentioning
confidence: 99%
“…Only sparse information is available on enzyme activities in human skeletal muscles [6,18,37,41,42,46,48]. Moreover, the determinations are from different muscles and from biopsies taken with different techniques which may influence the level of activity.…”
Section: Discussionmentioning
confidence: 99%